An ultrafast IR study of cytosine-rich nucleic acids and a photophysical study of porphyrin-nucleic acid systems - Keane, Páraic M (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
Work is presented in this thesis on two separate but complementary topics in the photochemistry of nucleic acids. Part one addresses the effect of direct UV excitation on the cytosine derivatives. Cytosine can form mutagenic dimers on exposure to sunlight, and this section examines the photophysical processes that occur in cytosine derivatives a few picoseconds after UV excitation. The experimental data is gathered primarily from the method of picosecond time-resolved infrared spectroscopy (ps-TRIR), with a particular interest in a non-emissive, relatively long-lived singlet nπ* excited state previously observed in some cytosine systems.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin